THE IMPACT OF LIFESTYLE FACTORS ON THE DEVELOPMENT OF TYPE 2 DIABETES MELLITUS - Sharafiy Tamina Floridovna (Web of Journals Publishing, 2025)
Type 2 Diabetes Mellitus (T2DM) is one of the most prevalent chronic metabolic disorders worldwide and represents a major public health challenge. The disease is strongly associated with lifestyle-related factors such as physical inactivity, unhealthy diet, obesity, and stress. This article aims to analyze the role of lifestyle factors in the development of T2DM and to emphasize the importance of preventive strategies. Understanding modifiable risk factors can significantly reduce the incidence of T2DM and improve overall health outcomes.
Keywords: Type 2 Diabetes Mellitus, lifestyle factors, prevention, obesity, physical activity.